Self-Talk and Affective Problems in College Students: Valence of Thinking and Cognitive Content Specificity - Calvete, Esther; Estévez, Ana; Landín, Covadonga; Martínez, Yolanda; Cardeñoso, Olga; Villardón, Lourdes; Villa, Aurelio (The Spanish Journal of Psychology, 2005)
The aim of this study was to develop a Self-Talk Inventory for young adults. This inventory consisted of two scales. The Negative Self-Talk Scale included three categories of selftalk (depressive, anxious, and angry thoughts) and the Positive Self-Talk Scale, three categories (minimization, positive orientation, and coping self-instructions). Participants were 982 undergraduate students (Mean age = 20.35 years, SD = 2.16). They completed the self-talk scales together with the following scales to measure symptoms of affective disorders: the Center for Epidemiological Studies Depression Scale (CES-D), the State- Trait Anxiety Inventory (STAI), and the State-Trait Anger Expression Inventory (STAXIT). Factor analyses confirmed the hypothesized structure for the Self-Talk Inventory. The relations between self-talk and symptoms of affective disorders (depression, anxiety, and anger) were also evaluated. In general, states-of-mind –SOM– ratios and negative cognitions showed a greater association with psychological symptoms than did positive cognitions.Results concerning the cognitive characteristics of depression, anxiety, and anger were mixed and partially supported the cognitive content specificity theory.